1990
DOI: 10.1109/48.103530
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically relevant bubble assemblages and their dependence on meteorological parameters

Abstract: Ab!ltraet-A detalled physical model of the Hfe history of a typical �ubble plume, from Its formation by a breakin& wave to its dissipation Into the background bubble population, is set down, and the relation ship between the early, acoustically relevant stages in bubble-plume development and the associat ed, remotely detectable whitecap is de scribed. The manner in which the fraction of the sea snrface covered by Stage A spilling crests and by Stage B mature whitecaps depends upon wind speed and upon wind stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 57 publications
2
91
0
1
Order By: Relevance
“…This suggests that, at a given wind speed in the field, bubble clouds with similar shapes and lateral extent would form in waters with different salinity. It is known that the bubble clouds sustain and replenish the whitecaps on the surface through the degassing of the bubbles in the bubble plumes [9,13,24,25]. Therefore, the implication of our results is that varying salinity would not affect the horizontal extent of the whitecaps supported by similarly shaped underwater bubble clouds.…”
Section: Implications For Air-sea Interaction Studiesmentioning
confidence: 50%
See 2 more Smart Citations
“…This suggests that, at a given wind speed in the field, bubble clouds with similar shapes and lateral extent would form in waters with different salinity. It is known that the bubble clouds sustain and replenish the whitecaps on the surface through the degassing of the bubbles in the bubble plumes [9,13,24,25]. Therefore, the implication of our results is that varying salinity would not affect the horizontal extent of the whitecaps supported by similarly shaped underwater bubble clouds.…”
Section: Implications For Air-sea Interaction Studiesmentioning
confidence: 50%
“…It is known that bubbles exist in the ocean in two populations. Bubbles in equilibrium, with diameters 2r less than 0.5 mm, form a layer of persistent background population about 1 m thick [24,25]. This background bubble population is constantly interacted upon by intermittent and relatively short-lived bubble clouds (plumes), representing the transient bubble population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under moderate wind conditions (> 3 m s −1 ) most bubbles near the ocean surface are generated by breaking waves (Thorpe and Humphries, 1980;Thorpe, 1982;Thorpe and Hall, 1983;Lamarre and Melville, 1991). Under mid-to high-wind conditions (wind speed > 7 m s −1 ), observationbased studies have shown a horizontal layer of subsurface bubbles that is formed and maintained by a constant supply of bubbles through breaking waves and turbulence (Crawford and Farmer, 1987;Monahan and Lu, 1990;Thorpe, 1982Thorpe, , 1986. While whitecaps are clear and obvious, they cover < 10 % of the ocean surface for winds as high as 20 m s −1 (e.g., Monahan et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Within a pixel of satellite observation, whitecaps are sporadic and scattered whereas bubbles in water form a more or less uniform layer that could exist over regions that are free from whitecap contamination (e.g., Monahan and Lu, 1990). While whitecaps serve as a diffuse reflector, reflecting solar radiation directly at the surface (Frouin et al, 1996;Whitlock et al, 1982), bubbles interact with light below the surface, enhancing water-leaving radiance (Stramski and Tegowski, 2001;Terrill et al, 2001;Zhang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%